Blind to midnight [large type] - Coleman, Reed Farrel, 1956- (Coleman, Reed Farrel, 1956- Nick Ryan series, 2024)
"When you're in trouble, you call 911. When cops are in trouble, they call Nick Ryan. Every cop in the city knows his name, but no one says it out loud. He doesn't wear a uniform, but he is the most powerful cop in New York. Nick Ryan can find a criminal who's vanished. Or make a key witness disappear. He has cars, safe houses, money, and weapons hidden all over the city. Nearly three thousand New Yorkers died on 9/ 11. But in the entire city on that tragic day, only one murder actually took place. Now, over two decades after, Detective Nick Ryan must dig beneath the official report--and into his own past--to find the truth. Working again for the mysterious power broker "Joe," Nick finds a link between an airman, a billionaire, a trove of Nazi gold, and a crew of killers, but gets sidetracked when his dear "uncle" Tony and Tony's wife are murdered in a professional hit. With professional killers on his trail, will Nick Ryan be able to end the violence before he loses everything that matters to him--including his own life?"--Provided by publisher.